Characterizing Exchange Rate Regimes in Post-Crisis East Asia - Baig, Taimur (IMF Working Papers; Working Paper, 2001)
This paper examines the behavior of the exchange rates of selected emerging market East Asian economies in the aftermath of the Asian crisis. The results suggest that movements in the Asia-5 currencies (Indonesia, Korea, Malaysia, Philippines, and Thailand) were significantly influenced by the U.S. dollar's day-to-day movements before the crisis, and have indeed continued to do so post-crisis. However, comparisons with a range of other currencies suggest that this is a fairly common trait across various regimes. Moreover, results from the post-crisis data do not support the view that the Asia-5 currencies presently have the same characteristics as they did before the crisis.